MODEL INDEKS TVDI (TEMPERATURE VEGETATION DRYNESS INDEX) UNTUK MENDETEKSI KEKERINGAN LAHAN BERDASARKAN DATA MODIS-TERRA - - Parwati; - Suwarsono (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2008)
Drought occurs when there is a lack of water in particular area and is usually caused by less amount of rainfall over that particular area. The impact of drought in Indonesia is usually noticed in the agricultural land. For that reason, agricultural drought monitoring in near-real time is very important. The TVDI (Temperature Vegetation Dryness Index) method is used in this research for agricultural drought monitoring. The TVDI is holding the information on the amount of soil moisture at the earth’s surface. The index is calculated from the surface temperature and the vegetation index. In this research, the TVDI model was developed from the enhanced vegetation index (EVI) and the land surface temperature (Ts) in Riau and Central Kalimantan Province using the Terra-MODIS in the period of June – August from 2003 to 2006. The formula are : Riau TVDI = (LST – (5.1912 * EVI + 294.72))/(-15.701 * EVI + 13.98), and Central Kalimantan TVDI = (LST – (0.498 * EVI + 296.97))/(-12.272 * EVI + 10.87). The model was then applied for detecting agricultural drought in Jambi Province and overlayed with landuse from LANDSAT ETM+ 2002/2003. The result showed that the paddy, dryland agriculture and plantation area are more sensitive to drought than shrub/bush. The mean values of TDVI are 0.40 and 0.34 for dryland agriculture/ plantation and paddy area respectively, while the shrub/bush is only 0.18. Based on the TDVI class for high drought (0.6  TVDI ≤ 1), it can be shown that from the periode of June-August 2003-2006, the large area of drought occurred in paddy area, plantation, and dryland agriculture was around 8 % in August, while the drought in the forest and shrub/bush area was narrow around 3 % in August. Further research can be done in order to know the accuracy, the verification, and the validation. Key words: MODIS, TVDI, EVI, LST (Land Surface Temperature)